Recovery markers in elite climbers after the national boulder climbing championship - Arthur Fernandes Gáspari; Arthur Fernandes Gáspari; Mayni Gabriele Zaminiani; Manoela de Carvalho Vilarinho; Danilo Caruso; Danilo Caruso; Patricia dos Santos Guimarães; Rafael Perlotti Piunti; Alex Itaborahy; Antonio Carlos de Moraes (Frontiers in Sports and Active Living, 2024)
This study aimed to investigate recovery markers among elite climbers following the National Boulder Championship. We assessed maximum isometric hand grip strength (HS), forearm swelling (circumference), delayed soreness in forearm muscles, tiredness, and exercise readiness at several time points: pre-competition, immediately post-competition (within 4 min after their last effort), and 12, 24, 48, and 60 h post-competition. Maximum isometric hand grip strength decreased by 6.38 ± 1.32% (p = 0.006) post-12 h, returning to pre-competition values post-24 h (all p > 0.05). Forearm circumference (FC) increased 1.78 ± 1.77% (p < 0.001) post-competition, returning to pre-competition values post-12 h (all p > 0.05). Forearm pain (FP) increased post-competition (p = 0.002) and post-12 h (p < 0.001), returning to pre-competition values post-24 h (all p > 0.05). Tiredness increased post-competition (p < 0.001), post-12 h (p < 0.001), and post-24 h (p < 0.001), returning to pre-competition values post-48 h (all p > 0.05). Climbing readiness was reduced post-competition (p < 0.001), post-12 h (p < 0.001), post-24 h (p < 0.001), and post-48 h (p = 0.005), only returning to pre-competition values post-60 h (p = 0.189). Visual analysis of individual data pointed out a relatively small variability in the HS and FC markers, while FP, tiredness, and readiness exhibited larger individual variations. These findings indicate that different recovery patterns exist for the analyzed markers, suggesting that athletes may require up to 60 h after a competition to fully recover and regain their ability to face new competitive challenges.